Personality of the Main Character in the Luca Movie Script - Putri, Kiki Islawati Anasti; Maca, Sudirman; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
The research aims at t finding out the sixth categories personality and focused on describe the factors behind the influenced of superiority feelings in Luca as a main character in the Luca movie script. The main theory of this study was individual psychology by Alfred Adler. The primary data sources used in this study was from Luca movie script that written by Jesse Andrews and Mike Jones. This study used descriptive qualitative analysis. The resultsofthis study shows that the main character in the Luca moviescript had sixth categories consist of fictionfinalism, inferiority feeling, striving for superiority, style of life, social interest, and creative power. The dominant personality changed was easily influenced because of Luca’s life style. Then, there were two factors that influence the superiority feelings which internal factors emerge based on the data social interest and creative power categories. Meanwhile, based on external factors, it appeared in the categories of fiction finalism and style of life. The dominant factors that easily influenced was external factors from style of life category